2007
DOI: 10.3168/jds.2007-0156
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Changes in the Association Between Milk Yield and Age at First Calving in Holstein Cows with Herd Environment Level for Milk Yield

Abstract: about the complexity of genetic association and genotype × environment interactions between AFC and MY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
9
3
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
10
9
3
6
Order By: Relevance
“…The phenotypic correlations between AFC and milk yield were very small and negative (−0.05). It is in accordance with other studies in which AFC and milk yield were estimated as small and negative (−0.20 to −0.09) (Ruiz-Sánchez et al, 2007;Ojango and Pollott, 2001;Nilforooshan and Edriss, 2004). However, Teke and Murat (2013) reported the moderate positive correlation between AFC and milk yield (r = 0.32; P<0.001).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The phenotypic correlations between AFC and milk yield were very small and negative (−0.05). It is in accordance with other studies in which AFC and milk yield were estimated as small and negative (−0.20 to −0.09) (Ruiz-Sánchez et al, 2007;Ojango and Pollott, 2001;Nilforooshan and Edriss, 2004). However, Teke and Murat (2013) reported the moderate positive correlation between AFC and milk yield (r = 0.32; P<0.001).…”
Section: Resultssupporting
confidence: 75%
“…Age at first calving determines the beginning of the cow's productive life and influences it's lifetime productivity (Ojango and Pollott, 2001). Ojango and Pollott (2001) and Ruiz-Sánchez et al (2007) indicated that earlymaturing heifers were better milk producers. According to Hoffman (1997) calving at less than 22 month of age had a negative influence on milk yield.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates for US Holsteins (0.03) (Cole & Null, 2010) and for Canada (0.09) (Jamrozik et al 2005) were also small, but not as small. Larger estimates above 0.20 were obtained in studies with different dairy breeds (e.g., Ruiz-Sánchez et al 2007). It is worth mentioning, however, that many of the estimates for this trait have been obtained with models lacking a sire-herd effect.…”
Section: Discussionmentioning
confidence: 99%
“…AFC in the present study was shorter than 47 months for crossbred cattle Amhara region as reported by Solomon et al (2009). Age at first calving have an impact on the productive life span of the cows and rearing cost of the dairy animals (Ruiz-Sanchez et al, 2007).…”
Section: Milking Productive and Reproductive Performance Of Dairy Cowsmentioning
confidence: 99%